The airway microbiome of persons with cystic fibrosis correlates with acquisition and microbiological outcomes of incident Stenotrophomonas maltophilia infection - Bowron, Lauren A.; Acosta, Nicole; Thornton, Christina S.; Carpentero, Jennifer; Waddell, Barbara-Jean M.; Bharadwaj, Lalit; Ebbert, Kirsten; Castañeda-Mogollón, Daniel; Conly, John M.; Rabin, Harvey R.; Surette, Michael G.; Parkins, Michael D. (Frontiers in Microbiology, 2024)
Rationale: Chronic infection with Stenotrophomonas maltophilia in persons with cystic fibrosis (pwCF) has been linked to an increased risk of pulmonary exacerbations and lung function decline. We sought to establish whether baseline sputum microbiome associates with risk of S. maltophilia incident infection and persistence in pwCF.Methods: pwCF experiencing incident S. maltophilia infections attending the Calgary Adult CF Clinic from 2010-2018 were compared with S. maltophilia-negative sex, age (+/-2 years), and birthcohort-matched controls. Infection outcomes were classified as persistent (when the pathogen was recovered in ≥50% of cultures in the subsequent year) or transient. We assessed microbial communities from prospectively biobanked sputum using V3-V4 16S ribosomal RNA (rRNA) gene sequencing, in the year preceding (Pre) (n=57), at (At) (n=22), and after (Post) (n=31) incident infection. We verified relative abundance data using S. maltophilia-specific qPCR and 16S rRNAtargeted qPCR to assess bioburden. Strains were typed using pulse-field gel electrophoresis.Results: Twenty-five pwCF with incident S. maltophilia (56% female, median 29 years, median FEV1 61%) with 33 total episodes were compared with 56 uninfected pwCF controls. Demographics and clinical characteristics were similar between cohorts. Amongst those with incident S. maltophilia infection, sputum communities didn't cluster based on infection timeline (Pre, At, Post). Communities differed between the infection cohort and controls (n=56) based on Shannon Diversity Index (SDI, p=0.04) and clustered based on Aitchison distance (PERMANOVA, p=0.01) prior to infection. At the time of incident S. maltophilia isolation, communities did not differ in SDI but clustered based on Aitchison distance (PERMANOVA, p=0.03) in those that ultimately developed persistent infection versus those that were transient. S. maltophilia abundance within sputum was increased in samples from patients (Pre) relative to controls, measuring both relative (p=0.004) and absolute (p=0.001). Furthermore, S. maltophilia abundance was increased in sputum at incident infection in those who ultimately developed persistent infection relative to those with transient infection, measured relatively (p=0.04) or absolute (p=0.04), respectively.Conclusions: Microbial community composition of CF sputum associates with S. maltophilia infection acquisition as well as infection outcome. Our study suggests sputum microbiome may serve as a surrogate for identifying infection risk and persistence risk.